Minimum Wage and Corporate Investment: Evidence from Manufacturing Firms in China - Geng, Heng (Griffin); Huang, Yi; Lin, Chen; Liu, Sibo (Journal of Financial and Quantitative Analysis, 2022)
This article studies how minimum-wage policies affect capital investment using the industrial census of manufacturing firms in China, where minimum-wage policies vary across counties. Exploiting discontinuities in minimum-wage policy at county borders, we find that minimum wages increase capital investment. The investment response to minimum wages is stronger for firms that are labor intensive, that have more room for technological improvement, and that cannot sufficiently pass on labor costs to consumers. A natural experiment based on county jurisdictional changes further assures the causal relationship.